Feasibility Study of a Microgrid for Electrifying the Isolated Area - Suka Alaqsa, Tengku Reza; Aini, Zulfatri; Eng, Ewe Win (Jurnal Edukasi Elektro, 2025)
Guha Village in Aceh Singkil lacks access to electricity from PLN, with challenging road conditions further complicating energy access. This study explores a feasible microgrid solution, assessing local renewable energy potential and economic viability using HOMER Pro software. Calculations reveal an annual energy demand of 97,334 kWh for 41 households. The analysis identifies a standalone micro-hydro system as the most cost-effective option, capable of partially meeting this demand with an annual output of 296,077 kWh. However, due to a distribution efficiency of 79.6%, the effective supply is 235,961 kWh per year. Financially, the micro-hydro system offers significant advantages, reducing the Net Present Cost (NPC) from Rp5.82 billion to Rp1.10 billion, despite a higher initial capital requirement of Rp825 million. With minimal O&M costs of Rp15 million annually and a Levelized Cost of Energy (LCOE) of Rp987.66/kWh, the system demonstrates substantial long-term savings. Investment metrics show a 49% Internal Rate of Return (IRR), 44% Return on Investment (ROI), and a two-year payback period, making the micro-hydro system a sustainable as cost effective energy solution for Guha Village.